An investigation into influence of acetylated cellulose nanofibers on properties of PCL/Gelatin electrospun nanofibrous scaffold for soft tissue engineering. (20th January 2021) - Moazzami Goudarzi, Zahra; Behzad, Tayebeh; Ghasemi-Mobarakeh, Laleh; Kharaziha, Mahshid
Abstract: In this study, the effective role of incorporation of cellulose nanofibers (CNF) and modified acetylated cellulose nanofibers (ACNF) on mechanical, physical, and biological properties of poly (ε-caprolactone) (PCL)/gelatin (Gel) electrospun nanofibrous scaffold was individually investigated. It was noticed that mechanical and biological properties of the scaffolds were considerably affected by the filler type and content. Although, by addition of 2 wt% ACNF, the ultimate tensile strength (UTS) of the PCL/Gel was remarkably enhanced from 2.5 ± 0.1 MPa to 4.3 ± 0.1 MPa due to homogeneous dispersion of the ACNF, however, the degradation rate of PCL/Gel scaffold was reduced about 1.66 times. Moreover, the studies on the interactions between hybrid scaffolds and fibroblast cells revealed that the incorporation of ACNF into scaffold not only showed no cytotoxic, but also promoted cell proliferation. In conclusion, PCL/Gel nanocomposite scaffolds reinforced by ACNFs show an excellent potential as a promising candidate for soft tissue engineering applications. Graphical abstract: Image 1 Highlights: Bionanocomposites scaffolds of PCL/Gel/ACNF were successfully fabricated by electrospinning method. ACNF incorporating significantly improved thermal and mechanical properties. Electrospun PCL/Gel/ACNF scaffolds exhibited a degradation behavior by none-toxic, biocompatible and biodegradable materials. Cell adhesion and proliferation of ACNF-loaded scaffolds were improved making it a candidate for soft tissue engineering.